A Review of Key Likert Scale Development Advances: 1995–2019 - Jebb, Andrew T.; Ng, Vincent; Tay, Louis (Frontiers in Psychology, 2021)
Developing self-report Likert scales is an essential part of modern psychology. However, it is hard for psychologists to remain apprised of best practices as methodological developments accumulate. To address this, this current paper offers a selective review of advances in Likert scale development that have occurred over the past 25 years. We reviewed six major measurement journals (e.g., Psychological Methods, Educational and Psychological Measurement) between the years 1995-2019 and identified key advances, ultimately including 40 papers and offering written summaries of each. We supplemented this review with an in-depth discussion of five particular advances: (1) conceptions of construct validity, (2) creating better construct definitions, (3) readability tests for generating items, (4) alternative measures of precision (e.g., coefficient omega and item response theory information), and (5) ant colony optimization for creating short forms. The supplemental material provides further technical details on these advances and offers guidance on software implementation. This paper is intended to be a resource for psychological researchers to be informed about more recent psychometric progress in Likert scale creation.